Frailty phenotype characteristics of Community-dwelling frail elderly people in a sub-district - Morarit, Sompong; Taypa, Kanjana; Boonyod, Witaya; Siviroj, Penprapa (Health Science, Science and Technology Reviews, 2018)
The study was aimed to determine the physical frailty phenotype among community-dwelling elderly people in a northern sub-district. The subjects of 48 frail elderly people (17.2%) were reported among 280 volunteers age of 60 years and more. In clinical practice frailty can be diagnosed using Fried criteria, requiring at least three of the five indicators: 1) unintentional weight loss (4.5 kilogram in past year); 2) selfreport exhaustion; 3) grip strength weakness; 4) slow walking speed; and 5) low physical activity. Two common phenotypic variances were poor muscle strength or hand grip weakness (87.5%), and exhaustion (83.3%), followed by slowness (68.8%), low physical activity (68.8%), and unintentional weight loss (25.0%), respectively.